1997
DOI: 10.1038/sj.bmt.1700752
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin therapy in bone marrow transplant recipients with viral respiratory tract infections

Abstract: Summary:enza B-virus and parainfluenza virus are less common but can contribute to increased morbidity and mortality. 2-9 A mortality rate of up to 78% has been reported for RSV Treatment with ribavirin was instituted in 12 allogeneic and one autologous bone marrow transplant (BMT) infection and pneumonia in BMT recipients. 10 Ribavirin (1-␤-d-ribofuranosyl-1,2-triazole-3-carboxrecipients with proven respiratory syncytial virus (RSV), influenza B virus or parainfluenza virus infecamide) is a synthetic nucleosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 1 publication
3
87
3
Order By: Relevance
“…8 Reported side effects included hemolysis, leukopenia and hyperbilirubinemia. 9,14,16 In our study, no related side effects were observed, which was consistent with previous studies reporting on the use of ribavirin in the hepatitis C infection setting. 17 Recently, Shah et al 6 reviewed and summarized the use of ribavirin from 26 available studies involving adult HSCT patients infected with RSV.…”
Section: Intravenous Ribavirin In Pediatric Hematopoietic Transplantasupporting
confidence: 81%
See 2 more Smart Citations
“…8 Reported side effects included hemolysis, leukopenia and hyperbilirubinemia. 9,14,16 In our study, no related side effects were observed, which was consistent with previous studies reporting on the use of ribavirin in the hepatitis C infection setting. 17 Recently, Shah et al 6 reviewed and summarized the use of ribavirin from 26 available studies involving adult HSCT patients infected with RSV.…”
Section: Intravenous Ribavirin In Pediatric Hematopoietic Transplantasupporting
confidence: 81%
“…In this regard, obstructive respiratory distress and dyspnea have been reported in patients receiving ribavirin inhalation therapy, leading to drug discontinuation. 14 14 3 Allogeneic (3) LRTI (3) ivR (1) Combined (2) No No NA 2 (66)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one study reporting the use of oral ribavirin for respiratory virus infections after HSCT. 11 However, the efficacy and required oral dose of ribavirin in HSCT are uncertain.…”
mentioning
confidence: 99%
“…[13][14][15][16] In one review, 13 RSV was found to be the responsible agent in 49% of cases, with just over half of these affecting the lower respiratory tract. Treatment options are either anti-viral, primarily using the virustatic agent, ribavirin or immunological, with the use of pooled or RSV specific immunoglobulin.…”
mentioning
confidence: 99%